Internet dan Ruang Publik Virtual, Sebuah Refleksi atas Teori Ruang Publik Habermas - Rulli Nasrullah (IKOM UMY, 2015)
Public sphere as popularized Habermas's a historicoL review of the criticol discussions in response to the political realities thot hoppen to people in the century -18. The emergence of the lnternet os a medium bari provide a broader transformation, both practicol and theoretical, of how public spoce took ploce in the virtual space. Charocteristics of the lnternet os o medium, users occess, to informotian thot is distributed in space (public) bosically becomes o virtual focal point to see how sesunggunyo character of public spoce in the virtuol world.